Evaluating and Ranking of Isfahan Provinces in Terms of Access to Health Sector Indicators - Hossein Ebrahimipour; Saeid Karimi; Jamil Sadighifar; javad Ebrahimzadeh; Mohammad Taghi Arman; Somaye Afshari (مدیریت اطلاعات سلامت, 2014)
Introduction: One of the most important dimensions of communities development is health development, in the other hand, is amount and quality of accessing of people to healthcare services. The purpose of this study is to evaluate and rank the Isfahan towns in terms of access to indices of health sector.